Asas Keadilan dan Ahli Waris Pengganti dalam Praktik Kewarisan Masyarakat berdasarkan Hukum Islam di Kecamatan Bantan Kabupaten Bengkalis - Hasan Basri; Muhammad Azani (Faculty of Law Hang Tuah University, 2017)
This article analyzes the inheritance practices carried out by the community in Bantan District, Bengkalis Regency Based on Islamic Law. The research method used is a sociological legal research that discusses the application of positive law regarding the practice of community inheritance in Bantan District, Bengkalis Regency. The results showed: a. The community in Bantan Subdistrict turned out to be wrong in understanding the principle of balanced justice which was considered to be contrary to the sense of justice for the heirs. They understand the principle of balanced justice must be in the same sense. Whereas the meaning of the principle is that each heir, both male and female, has the same rights in obtaining inheritance rights. Men get more rights which do not mean unfair, but in Islamic law it stipulates that men are responsible for the burden of the family; b. The community in Bantan District in understanding radd in Islamic law does not fully refer to the KHI which is a reference in determining the law. They divide radd based only on habits that can be shared with the heirs who want it or the mosque; c. The community in Bantan Subdistrict considers that the heirs who passed away first from the heir, cannot be replaced by the heir's child. Whereas based on Article 185 paragraph (1) the KHI position of the heir can be replaced by the offspring of both male and female.